(untitled) (Journal of the College of Basic Education, 2026)
The most important reason for choosing this research is the qualitative value of this novel, in which time and place have an important semiological reflection. Therefore, the research addresses the duality of the familiar and the hostile place and its semiological reflection on the novel "Tashari" by Inaam Kachachi. The research identifies the positions that made this place familiar or hostile. We found the place to be a symbol that depicts Iraqi society and its peaceful coexistence through its being a familiar place. The hostile place also depicted the extent of the oppression and fragmentation of the Iraqi person in exile, and showed us the extent of the disintegration of Iraqi families due to migration outside the homeland. The semiological reflection of these places worked to generate meaning as a subject within a text to generate new meanings, through the semantic function of the sign within the narrative text. The most important problem of the research is the scarcity of sources that address such a thorny topic that combines the semiological importance of place and time, and their semiological reflection on the character who represents the spirit of religious minorities in Iraq. Therefore, the research succeeded in breaking the stereotype between the other and his place of presence with the majority. The heterogeneous majority has become a familiar place for the heroine’s character, as she belongs to the different other, while the place where the majority that matches the heroine’s character resides has become a hostile place, as is clear in the city of Paris